Cronic Kidney Disease, Life Quality Assessment Of Patients - Duli, Marsida; Dika, Qamil; Bushati, Matilda (European Scientific Journal, ESJ, 2016)
Assessing quality of life in patients with varying degrees of chronic kidney disease is an important issue because of its impact on clinical decision-making as increasing the efficiency of resources in the health system. Through this survey provided an attempt to assess the quality of life of patients with chronic kidney disease undergoing dialysis. Commitment to maximize their functioning and well-being constitutes the essence of the purpose of health care. In recent decades elaborate SF 36 is cut by a gauge derive so simple and basic that helps to evaluate the function of the target of researchers, a certain age group, a disease or a treatment group. Short questionnaire forms SF36 instrument gauge is used to determine the level of quality of life in patients with chronic renal failure under the different stages of treatment with dialysis. The study involved 206 people, 112 from patients to Tirana and Shkodra and 94 healthy persons, who collaborated consensually for completing the questionnaires. Based on the results, the quality of life of dialysis patients is significantly worse than that of the healthy population and patients with other injuries less severe of renal function. Survey indicates that a more holistic approach to be used in the treatment of patients with chronic kidney disease including clinical decision making and patient perception. Precisely for this it is recommended to enter the practice of clinical interest that a set of questionnaires that provide information on patients’ perception of health as an important indicator that facilitates the physician-patient collaboration in order to better treatment of the disease and increase the quality the life of the patient.